2021
DOI: 10.1111/obr.13370
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and progress of lean body mass, fat‐free mass, and skeletal muscle mass loss following bariatric surgery: A systematic review and meta‐analysis

Abstract: Postbariatric loss of muscle tissue could negatively affect long-term health due to its role in various bodily processes, such as metabolism and functional capacity. This meta-analysis aimed to unravel time-dependent changes in the magnitude and progress of lean body mass (LBM), fat-free mass (FFM), and skeletal muscle mass (SMM) loss following bariatric surgery. A systematic literature search was conducted in Pubmed, Embase, and Web of Science. Fifty-nine studies assessed LBM (n = 37), FFM (n = 20), or SMM (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 104 publications
4
39
0
Order By: Relevance
“…Such a decrease in muscle strength can be primarily attributed to the loss of lean body mass, which itself is due to the dramatic decrease in protein intake observed in the first months following bariatric surgery [27,39]. Interestingly, our study and others [40,41] showed that rates of lean body mass loss were higher during the first 3 to 6 months after RYGB, characterized by very low protein intake [27,39], followed by a more gradual decrease up to 12 months. Our initial trial showed that combining resistance training and protein supplementation was however insufficient to counteract the effect of bariatric surgery on lean body mass loss during the first post-operative months [27].…”
Section: Plos Onesupporting
confidence: 51%
“…Such a decrease in muscle strength can be primarily attributed to the loss of lean body mass, which itself is due to the dramatic decrease in protein intake observed in the first months following bariatric surgery [27,39]. Interestingly, our study and others [40,41] showed that rates of lean body mass loss were higher during the first 3 to 6 months after RYGB, characterized by very low protein intake [27,39], followed by a more gradual decrease up to 12 months. Our initial trial showed that combining resistance training and protein supplementation was however insufficient to counteract the effect of bariatric surgery on lean body mass loss during the first post-operative months [27].…”
Section: Plos Onesupporting
confidence: 51%
“…Other successful obesity treatments, such as bariatric surgery, do not appear to require lifestyle modifications to provide any more weight loss within the first year after surgery [ 31 , 32 ]. This may be due to the subject’s obesity being effectively treated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another major unexplored consequence of >15% weight loss with semaglutide may be the inevitable lean muscle mass loss. This is also evident after liraglutide and bariatric surgery [ 32 , 33 , 34 , 35 ]. The challenge is that patients who consume so few calories because of the effective medication cannot consume enough protein in their daily intake to stop them from becoming catabolic and losing muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have undergone bariatric surgery are prone to changes in weight, BMI, and lean body mass up to 10 years after surgery 50,51 . Studies in our review varied widely in their duration of follow‐up, with many studies reporting a follow‐up period of less than 30 days.…”
Section: Knowledge Gaps and Research Agendamentioning
confidence: 99%
“…Patients who have undergone bariatric surgery are prone to changes in weight, BMI, and lean body mass up to 10 years after surgery. 50,51 Studies in our review varied widely in their duration of follow-up, with many studies reporting a follow-up period of less than 30 days. Future studies with longer and more consistent follow-up are warranted to improve the precision of our estimates and to explore how or whether DOAC pharmacokinetics change over time in this population.…”
Section: K Nowledg E G Aps and Re S E Arch Ag En Damentioning
confidence: 99%